Putting liberalism in its place - Kahn, Paul W., 1952- (Princeton University Press, 2008)
In this wide-ranging interdisciplinary work, Paul W. Kahn argues that political order is founded not on contract but on sacrifice. Because liberalism is blind to sacrifice, it is unable to explain how the modern state has brought us to both the rule of law and the edge of nuclear annihilation. We can understand this modern condition only by recognizing that any political community, even a liberal one, is bound together by faith, love, and identity.